Pig target detection method based on SSD convolution network. Issue 2 (April 2020) - Deng, Minghui; Yu, Ran
Abstract: The behavioral changes of pigs can not only reflect their own health and welfare status, but also have important significance in improving the breeding environment. Rapid and accurate detection of pigs' targets is the basis of behavioral change analysis.In view of this situation, a target detection algorithm based on deep learning is proposed, and its model structure and working principle are expounded. Then, through the test of pig image data set, the results show that this method can accurately detect pig targets under complex background.